Paleogeography and biogeography of the Gondwanan final breakup and its terrestrial vertebrates: New insights from southern South America and the "double Noah's Ark" Antarctic Peninsula - Reguero, Marcelo Alfredo; Goin, Francisco Javier (Journal of South American Earth Sciences)
The Mesozoic plate tectonic and paleogeographic history of the final break up of West Gondwana had a profound effect on the distribution of terrestrial vertebrates in South America. As the supercontinent fragmented into a series of large landmasses (South America, Antarctica, Australia, New Zealand, the Indian subcontinent, and Madagascar), particularly during the Late Jurassic and Cretaceous, its terrestrial vertebrates became progressively isolated, evolving into unique faunal assemblages. The episodic nature of South American mammalian Cenozoic faunas became apparent in its modern formulation after George Gaylord Simpson´s seminal works on this topic. Two aspects add complexity to this generally accepted scheme: first, the fact that South America is not (and was not) a biogeographic unit, as the Neotropical Region does not include its southernmost tip (the Andean Region, including Patagonia and the southern Andes). Second, and intimately linked with the first one, that South America was not an island continent during the Late Cretaceous and the beginning of the Cenozoic, being its southernmost portion closely linked with West Antarctica up to the late Paleocene at least. Here we stress on this second aspect; we summarize a series of recent, detailed paleogeographical analyses of the continental breakup between Patagonia (including the Magallanes Region) and the Antarctic Peninsula crustal block, beginning with the opening of the Atlantic Ocean in the Early Cretaceous and running up to the Early Paleogene with the expansion of the Scotia Basin. In second place, we comment on the implications of these distinct paleogeographic and paleobiogeographic scenarios (before and after their geographic and faunistic isolation) for the evolution of South American terrestrial mammalian faunas. Summarizing, (1) we recognize a West Weddellian terrestrial biogeographic unit with the assemblage of the southern part of South America (Patagonia and the Magallanes Region) and the Antarctic Peninsula (and probably Thurston Island) ...